Interfaces in Garnet‐Based All‐Solid‐State Lithium Batteries. Issue 39 (4th September 2020) - Wang, Dawei; Zhu, Changbao; Fu, Yanpeng; Sun, Xueliang; Yang, Yong
Abstract: All‐solid‐state lithium batteries (ASSLBs) are considered to be the next‐generation energy storage system, because of their overwhelming advantages in energy density and safety compared to conventional lithium ion batteries. Among various systems, garnet‐based ASSLBs are one of the most promising candidates. The advantages arise from the intrinsic properties of garnet electrolytes, especially the high shear modulus and wider electrochemical window compared to that of polymer and sulfide electrolytes, guaranteeing the application of Li metal and high voltage cathodes. However, the interfacial issues between garnets and electrodes (Li metal and cathodes) are challenging and hinder the further development of garnet‐based ASSLBs. Herein, the origin of interfacial resistance and recent development of interfacial construction in garnet‐based ASSLBs are reviewed, as well as the subsequent interfacial degradation and cell failure during cycling process, including inhomogeneous plating and stripping, Li dendrites, and strain induced microcracks in stiff electrodes. Finally, the future challenges and opportunities in this important and exciting field are also presented. Abstract : Garnet‐based all‐solid‐state lithium batteries will be promising next generation energy storage system once the interfacial issues are solved. The interfacial issues include the large interfacial resistance at the initial state and the mechanical degradation of both anodic and cathodic interfaces during the subsequent cycling process. Ingenious architecture design and advanced engineering technique can help to build a better all‐solid‐state lithium battery.